Robustness Analysis of GWO/PID Approach in Control of Ball Hoop System with ITAE Objective Function - Porwal, Mridul; Parmar, Girish; Bhatt, Rajesh (International Journal of Computer Sciences and Engineering, 2018)
This work deals with robustness analysis of Grey Wolf Optimization (GWO) / Proportional-Integral-Derivative (PID) approach in control of ball hoop (BH) system with integral of time multiplied absolute error (ITAE) objective function. The robustness analysis of GWO/PID approach has been carried out with ±5% perturbation in the locations of the poles of the BH system. It has been observed that proposed GWO/PID approach with ITAE objective function gives satisfactory performance with ±5% perturbation.